Three-dimensional conductive conjugated polyelectrolyte gels facilitate interfacial electron transfer for improved biophotovoltaic performance - Zhongxin Chen; Samantha R. McCuskey; Weidong Zhang; Benjamin Rui Peng Yip; Glenn Quek; Yan Jiang; David Ohayon; Shujian Ong; Binu Kundukad; Xianwen Mao; Guillermo C. Bazan (Nature Communications)
Abstract Living biophotovoltaics represent a potentially green and sustainable method to generate bio-electricity by harnessing photosynthetic microorganisms. However, barriers to electron transfer across the abiotic/biotic interface hinder solar-to-electricity conversion efficiencies. Herein, we report on a facile method to improve interfacial electron transfer by combining the photosynthetic cyanobacterium Synechococcus elongatus PCC 7942 (S. elongatus) with a conjugated polyelectrolyte (CPE) atop indium tin oxide (ITO) charge-collecting electrodes. By self-assembly of the CPE with S. elongatus, soft and semitransparent S. elongatus/CPE biocomposites are formed with three-dimensional (3D) conductive networks that exhibit mixed ionic-electronic conduction. This specific architecture enhances both the natural and mediated exoelectrogenic pathway from cells to electrodes, enabling improved photocurrent output compared to bacteria alone. Electrochemical studies confirm the improved electron transfer at the biotic-abiotic interface through the CPE. Furthermore, microscopic photocurrent mapping of the biocomposites down to the single-cell level reveals a ~ 0.2 nanoampere output per cell, which translates to a 10-fold improvement relative to that of bare S. elongatus, corroborating efficient electron transport from S. elongatus to the electrode. This synergistic combination of biotic and abiotic materials underpins the improved performance of biophotovoltaic devices, offering broader insights into the electron transfer mechanisms relevant to photosynthesis and bioelectronic systems.